1970
DOI: 10.3126/kumj.v8i2.3560
|View full text |Cite
|
Sign up to set email alerts
|

Upper gastro-intestinal bleeding: Aetiology and demographic profile based on endoscopic examination at Dhulikhel Hospital, Kathmandu University Hospital

Abstract: Background: The upper gastrointestinal bleeding (UGIB) is defi ned as bleeding within the intraluminal gastrointestinal tract from any location between the upper oesophagus to the duodenum at the ligament of Treitz. It is one of the important medical emergencies worldwide. Objective: The objective of this study is to study the aetiology of upper gastrointestinal bleeding based on endoscopic examination fi ndings in patients of various demographic characteristics. Materials and methods: This is a retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 0 publications
3
26
2
Order By: Relevance
“…In other parts of Nepal also, male predominance was reported by Bhattarai et al 71% and Gurung et al 64.4%. 8,14 Similarly in other studies also male to female ratio 3:1 and 3.2:1, 70.1% male in Jamaican study, 79% male in Sudan study, 78.4% males reported by Kashyap et al and 59% in UK audit. [9][10][11][12][13]15 In Nepal various risk factors like smoking and alcohol consumption that are commoner in male population might have some role in the contribution to UGI bleeding.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In other parts of Nepal also, male predominance was reported by Bhattarai et al 71% and Gurung et al 64.4%. 8,14 Similarly in other studies also male to female ratio 3:1 and 3.2:1, 70.1% male in Jamaican study, 79% male in Sudan study, 78.4% males reported by Kashyap et al and 59% in UK audit. [9][10][11][12][13]15 In Nepal various risk factors like smoking and alcohol consumption that are commoner in male population might have some role in the contribution to UGI bleeding.…”
Section: Discussionmentioning
confidence: 61%
“…In the present study, mean age was 48.76+17.19 which is similar to studies reported by from Nepal Gurung et al and Hussein et al that showed mean age 45.32+18.47 years and 44.6 years respectively. 8,9 From India, Anand et al reported mean age being 41 years and Rao et al reported a mean age of 43 years, from West Indies, Kaliamurthy et al reported higher mean age of 55 years. [10][11][12] Recent published UK audit showed even higher mean age of 64.4.…”
Section: Discussionmentioning
confidence: 99%
“…71% similar to other parts of Nepal. 4,5 Some other studies 6,7,8,11,12 have also shown male predominance. In Southeast Asian countries, various risk factors like smoking, heavy alcohol consumption, alcoholic liver disease and low socioeconomic status might have some role in the contribution to UGI bleeding.…”
Section: Discussionmentioning
confidence: 86%
“…[22] A study by Bedi TRS et al, Kathmandu, Nepal found hematemesis (56.7%), maelena (14.4%), recent onset anaemia with positive occult blood (22.2%) and both haemetemesis and maelena (6.7%) as presenting features. [23] Another study from northwestern Tanzania by Hyasinta et al found that the vast majority of patient presented with hematemesis (80.4%) alone. Maelena alone was reported in 9.2% patients.…”
Section: Introductionmentioning
confidence: 97%